2021
DOI: 10.14712/23362936.2021.22
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring of Protein Kinase Inhibitors in Breast Cancer Patients

Abstract: Protein kinase inhibitors (PKIs) represent up-to-date therapeutic approach in breast cancer treatment. Although cancer is a rapidly progressive disease, many substances, including PKIs, are usually used at fixed doses without regard to each patient’s individuality. Therapeutic drug monitoring (TDM) is a tool that allows individualization of therapy based on drug plasma levels. For TDM conduct, exposure-response relationships of drug substances are required. The pharmacokinetic data and exposure-response eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…10 Target C min values of abemaciclib (200–210 ng/mL) and ribociclib (711 ng/mL) for TDM have also been proposed but require confirmation in prospective studies. 11 In addition to TDM, a bioanalytical assay for CDK4/6 inhibitors would also be useful for pharmacogenetic studies. As reported most recently for palbociclib, polymorphisms could be associated with the pharmacokinetics and/or pharmacodynamics of CDK4/6 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…10 Target C min values of abemaciclib (200–210 ng/mL) and ribociclib (711 ng/mL) for TDM have also been proposed but require confirmation in prospective studies. 11 In addition to TDM, a bioanalytical assay for CDK4/6 inhibitors would also be useful for pharmacogenetic studies. As reported most recently for palbociclib, polymorphisms could be associated with the pharmacokinetics and/or pharmacodynamics of CDK4/6 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…In a review, Falkowski and Woillard (2019) reported that a trough concentration higher than 20 ng/ml could be proposed as a threshold to indicate an increased risk of overall severe toxicity. Furthermore, Roušarová et al (2021) reported that a trough concentration between 10 and 20 ng/ml was a promising therapeutic drug monitoring target for everolimus in breast cancer treatment, in a review of therapeutic drug monitoring of protein kinase inhibitors in patients with breast cancer. The findings from these reports support our study’s findings.…”
Section: Discussionmentioning
confidence: 99%
“…39 A relationship between exposure and response and/or safety has been established and therapeutic targets have already been reported for some drugs. 40,41 Systemic physiologic changes are very dynamic in AKI patients. Drug clearance and distribution vary in the short term (some hours and days) and it is difficult to practically quantify the glomerular filtration rate (GFR) 42 as well as liver metabolism.…”
Section: Impact Of Kidney Pathologies On Tki Pharmacokineticsmentioning
confidence: 99%